Board effectiveness of Malaysian small and medium enterprises (SMEs) - Mohd Adi, Mohd Nazir (2022)
Over the past three decades, there has been a considerable number of corporate governance research. Most researchers found that SMEs are marginalised, and without clear guidelines, unscrupulous directors are most likely to breach trust. The primary objective of this study is to develop a new framework of board effectiveness for Malaysian SME boards. The current study employs a qualitative design to investigate the research objectives through the lens of a phenomenological approach. The information was gathered through eighteen semi-structured interviews. In addition, secondary data from a hundred E50 award recipients were analysed to support the findings. The data was analysed using thematic analysis, which was carried out using NVivo 12 plus. As a result, the key findings of the studies are that for the SME board to function effectively, (1) Directors must have a broad range of knowledge and skills in various areas, including business management, finance, basic legal corporations, firm-specific knowledge, and others. (2) The board should comprise the optimal number of directors. (3). The board’s behaviour debate, teamwork, leadership, commitment, involvement, integrity, employee engagement, openness, and wisdom are essential. (4) Furthermore, the decision of the meeting must consider the opinions of the majority of the attendees. Lastly (5), it is also important to consider the tasks and roles of the board, which include the following: vision and mission; finance; human resource management; management; marketing; production and operation; strategic planning; fiduciary responsibilities; succession planning; and separation of powers. To sum up, Malaysian SMEs require a comprehensive, and integrated corporate governance policy or guidelines that reflect a holistic board effectiveness mechanism. The study also recommends that policymakers carefully consider the specific fundamental roles that directors must play to carry out their responsibilities.